Carbon fibers having a nano-arched structure on Co-supersaturated Cu foils. (June 2019) - Odaira, Takumi; Kameoka, Satoshi; Aono, Masami; Terauchi, Masami; Tsai, An-Pang
Abstract: A unique nano-arched carbon fiber (NACF) structure was formed on Cu-1at.%Co foil prepared by melt-spinning. NACFs were generated in a flow of a C2 H4  + H2 (1:1) mixture at both 823 and 873 K on the surfaces of Co particles embedded in the Cu foil. Each NACF was a bundle of a large number of small rods that gradually changed their longitudinal orientations along the [001] graphite growth direction. These NACFs were only obtained in conjunction with the in situ growth of Co particles, indicating dynamic, simultaneous growth of the carbon fibers and Co particles. Graphical abstract: Image 1